Compound Heterozygous Variants in the Coiled-Coil Domain Containing 40 Gene in a Chinese Family with Primary Ciliary Dyskinesia Cause Extreme Phenotypic Diversity in Cilia Ultrastructure - Yang, Lin; Banerjee, Santasree; Cao, Jie; Bai, Xiaohong; Peng, Zhijun; Chen, Haixia; Huang, Hui; Han, Peng; Feng, Shunyu; Yi, Na; Song, Xueru; Wu, Jing (Frontiers in Genetics, 2018)
Abstract Purpose: Primary ciliary dyskinesia (PCD) is a rare genetic disorder manifested with recurrent infections of respiratory tract and infertility. Mutations in more than 20 genes including the Coiled-Coil Domain Containing 40 （CCDC40）gene are associated with PCD. A Chinese proband with a clinical diagnosis of PCD was analysed for mutations in these genes to identify the genetic basis of the disease in the family. The proband showed altered mucociliary clearance of the airways, various degree of hyperemia and edema of the mucous membrane, left/right body asymmetry, infertility and ultrastructural abnormality of cilia in both sperm and bronchioles. Methods: The DNA from the proband was analyzed for genetic variation in a subset of genes known to cause PCD using targeted next generation sequencing in order to understand the molecular and genetic basis of the PCD in present family. The result of targeted next generation sequencing has been validated by Sanger sequencing and q-PCR. Results: Targeted next-generation sequencing identified two novel mutations (c.1259delA and EX17_20 deletion) in CCDC40 gene that causes abnormal CCDC40 mRNA expression. These two novel variants cause disorganization of axoneme filaments ,which resulted in reduction of sperm motility and phenotypic diversity in ultrastructure of cilia in the proband. Conclusion: These findings highlight the significance of the mutations in CCDC40 as novel candidates for genetic testing in PCD patients as well as the key role of ICSI treatment for the families affected by this ciliary dysmotility. Our findings showed that our work enriched the performance of cilia ultrastructure which were not previously reported in PCD patients.